La gobernanza en el deporte: la legitimidad en la federación colombiana de atletismo un estudio de caso de tipo explicativo (2019)
The purpose of this article is focus on determine the state of Governance - Legitimacy in the Colombian Athletics Federation, and, likewise, its level of development with the International Federation. The study’s objective focuses on the evaluation of the Colombian Athletics Federation (sports leagues, the Colombian Olympic Committee and Coldeportes). All data obtained was collected through the observation document generated by the "Play the Game" association and adjusted to the needs of the national sports system. Methodologically, this study, was divided into three phases. In the first phase, the origin of the research was described, and a conceptual framework was developed, which goes from the general to the, to finally focus on theAthletics national Federation. In the second phase, the execution of the instrument "Sports Governance Observer 2015: the legitimacy crisis in international sports governance" was carried out. In the third phase, an analysis of the instrument, to obtain conclusions about the status of each indicator. The data and results are presented according to each of the indicators evaluated by the instrument used. In addition, it is necessary to clarify that, according to the bibliography review, 9,668 articles were found. However, they have never been found as functional: Scopus (1), ProQuest (18), Science direct (5), Sportdiscus (1), Google academic (10).